Survei Minat dan Bakat Atlet Hockey di Kabupaten Garut - Ramdhani, Adam; Hermawan, Irwan; Permadi, Asep Angga; Kosasih, Alam Hadi (Jurnal Porkes, 2025)
The purpose of this study is to examine the level of interest and talent in hockey in Garut Regency. This is a non-experimental descriptive quantitative study conducted through surveys and tests. The sample size for this study was 40 people, representing the entire population of hockey athletes in Garut Regency. The sampling technique used was simple random sampling. The data analysis technique used in this study was statistical analysis using percentages. The instruments used were interest and talent tests. The percentage results were 76.98% for male athletes and 79.76% for female athletes, with each aspect having its own percentage: 71.98% for male athletes in the high category and 76.62% for female athletes in the high category. The percentage for motivation was 77.51% for male athletes in the high category and 80.80% for female athletes in the high category. The percentage for feelings was 77.08% for male athletes in the high category and 85.76% for female athletes in the very high category. The percentage for goals was 80.95% for male athletes in the high category and 76.94% for female athletes in the high category. For the results of the talent assessment, male hockey athletes are in the good category with a percentage of 88.33%, while female hockey athletes are in the good category with a percentage of 86%. The talent of hockey athletes in Garut Regency can be concluded that the level of interest in hockey athletes in Garut Regency is in the high and good categories.